Evaluation of Pain Management in Post-Spinal Decompression and Posterior Stabilization Patients: Case Study - Yudianto, Kurniawan; Fernanda, Ni Putu Mulia (Journal of Nursing Care, 2024)
Postoperative pain needs to be a concern for nurses because pain causes discomfort, one of the basic human needs. Untreated postoperative pain can affect quality of life and the recovery process. With a management approach, the nursing process can be integrated with the management process. Control and evaluation as part of the management process is important because at this stage the nursing manager can determine the quality of care provided. This case study aims to describe the use of the Revised American Pain Society Patient Outcome Questionnaire (APS-POQ-R) in evaluating pain management. Patient was admitted with post-spinal decompression and posterior stabilization e.c tuberculosis spondylitis. Pain management includes observing pain, deep breathing relaxation techniques and praying/dzikir, providing education about the causes, triggers, and strategies to relieve pain, as well as providing collaborative measures of ketorolac analgesics. Evaluation of pain management with this questionnaire was carried by researcher out in the first 24 hours postoperative. After receiving pain management, an overview of the severity and reduction of patient pain, the impact of pain on activity, sleep, and negative emotions, the side effects of using ketorolac, the usefulness of information about pain management, the patient's ability to participate in pain treatment decisions, and use of non-pharmacological strategies. The APS-POQ-R can be used to evaluate of six aspects of patient pain management.